Empowering Legal Advocacy for Social Justice in Indonesia: Memberdayakan Advokasi Hukum untuk Keadilan Sosial di Indonesia - Achmad, Fandi; Fatimah, Noor (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background:The Legal Assistance and Consultation Institute (LKBH) is vital in supporting the Muhammadiyah organization through comprehensive legal services, addressing both internal and external legal challenges. Specific Background:LKBH's role in Muhammadiyah's legal complexities is significant, but research on its effectiveness is limited, highlighting the need for further investigation. Knowledge Gap:Current literature lacks a detailed exploration of how LKBH’s services contribute to resolving legal issues and strengthening the organization’s legal standing amidst Indonesia's socio-political dynamics. Aims:This study aims to analyze the challenges faced by Muhammadiyah, examine LKBH's strategies in addressing these challenges, and evaluate the impact of its legal services on the organization's sustainability and mission. Results:Through qualitative methods, including case analysis, surveys, and interviews, the findings highlight LKBH’s effective legal interventions and educational initiatives, which significantly enhance members’ legal awareness and compliance.Novelty:This research provides new insights into the multifaceted role of LKBH within Muhammadiyah, emphasizing its contributions not only to legal enforcement but also to organizational integrity and public advocacy.Implications:The study underscores the importance of LKBH in promoting social justice and formulating progressive policies, thereby positioning Muhammadiyah as a proactive player in Indonesian society, committed to the welfare of its members and the broader community. Highlights: Comprehensive Support: LKBH addresses Muhammadiyah's internal and external legal challenges effectively. Legal Education: Enhances legal awareness and compliance among Muhammadiyah members. Advocacy Role: Promotes social justice and progressive policies for community welfare Keywords: Legal assistance, Muhammadiyah, LKBH, advocacy, legal education.